Muscles Activity in the elderly with Balance Impairments in walking under Dual tasks - Elaheh Azadian; Hamidreza Taheri Torbati; Alireza saberi Kakhki (Biyumikānīk-i varzishī, 2016)
Objectives: Each step during gait requires different attention demands that will affect muscles activity. The study of changes in the timing and intensity of the muscles activity in walking with dual task has received less attention from researchers. The purpose of this study was to evaluate changes in electromyography patterns of gait with cognitive dual tasks in balance impaired elderly.